Influência do hipoclorito de cálcio sobre a resistência de união entre a resina composta e dentina - Costa, Marielle Azevedo Sehn da (2012)
The aim of this study was to evaluate the tensile bond strength (μTBS) of composite to dentin after different surface treatments and the fracture pattern under optical microscope and MEV, testing the hypothesis that mean μTBS values are similar for all dentin surface treatments evaluated. Forty five third human molars were cut to expose a flat occlusal dentin surface. The teeth were randomly divided into three groups (n=15): G1 (control): 37% phosphoric acid for 15s (AE) + Prime & Bond 2.1 (PB); G2: AE + 10% sodium hypochlorite (NaOCl) for 15s + PB; G3: AE + 10% Calcium hypochlorite (CaOCl) for 15 s + PB. Six mm-thick composite resin restorations were built and the teeth were cut in bar-shaped specimens, with a cross-sectional area (A) of about 1mm2. Two specimens from each tooth (n=30) were randomly selected for testing in tension (μTBS) until fracture (cross-head speed: 0,5 mm/min). Data (in MPa) were statistically analyzed using Anova (α= 0.05). Fractographic principles were applied to examine fractured surfaces of five specimens of each group (n=5) in stereo microscope (40X) and MEV. Mean and standard deviation values were: G1 = 28,68±12,52a; G2 = 25,80±11,77a; G3 = 21,28±9,22a. Results showed no significantly differences among experimental groups, confirming the study hypothesis. Group G3 showed that 100% of fractures had originated within the adhesive area, while G1 and G2 had 40% of adhesive failures and 60% cohesive in resin or dentin. It was possible to conclude that the dentin deproteinization treatment using CaOCl (G3) showed mean μTBS values comparable with conventional technique (G1) and with NaOCl deproteinization treatment (G2)